1992
DOI: 10.1128/aac.36.12.2778
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerases from pathogenic fungi: targets for the discovery of antifungal drugs

Abstract: (11,19,20,36,60DNA break to form a gate allowing subsequent DNA strand passing. Effective topoisomerase inhibitors stabilize the intermediate, termed the cleavage complex, and this stabilization in the cell triggers an unknown process causing cell death (7,30). The stabilization of the cleavage complex by topoisomerase inhibitors thus converts these enzymes into cellular poisons (28). The strategy of discovering therapeutic agents of this class is, therefore, plausible and easily justifiable because of the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 44 publications
(26 reference statements)
1
49
0
Order By: Relevance
“…These results are in agreement with previous studies using a partially purified topoisomerase II preparation from C. albicans and calf thymus topoisomerase II as a representative mammalian enzyme [26]. Differential DNA cleavage was reported for four compounds, and similar or lower levels of DNA breakage were observed for the fungal enzyme in most cases, e.g.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are in agreement with previous studies using a partially purified topoisomerase II preparation from C. albicans and calf thymus topoisomerase II as a representative mammalian enzyme [26]. Differential DNA cleavage was reported for four compounds, and similar or lower levels of DNA breakage were observed for the fungal enzyme in most cases, e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Purification of C. albicans topoisomerase I and its inhibition by aminocatechols have been reported and the corresponding TOP1 gene has been characterized [23][24][25]. In the case of C. albicans topoisomerase II, only one paper has appeared that describes a partial purification procedure [26]. By using this preparation in parallel with mammalian topoisomerase II, the authors identified one compound, a quinolone derivative, that preferentially inhibited the fungal enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, there are already a series of genes in C. neoformans associated with infection and their quantitative and qualitative impact on virulence has been described through gene disruption experiments. These genes include those for the following: capsule formation (8)(9)(10)(11)27), melanin production (20,31,49), high-temperature growth (36,48), purine metabolism (47), myristylation (32), topoisomerase (54), signal transduction (2,3,12,18,41,55), alpha-mating type locus (30), phospholipase (13), urease (14), and mannosylation (57). In addition to a single gene disruption strategy, a more global approach has used signature-tagged mutagenesis to identify virulence genes (40).…”
mentioning
confidence: 99%
“…Several studies have suggested that DNA topoisomerase is a potential target of antifungal agents [12][13][14][15]16] found that the DNA topoisomerase inhibitor aclarubicin at 0.8-7.3 µg/mL inhibited the growth of C. albicans in vitro, whereas other inhibitors, including daunorubicin, doxorubicin, idarubicin, beta-lapachone, camptothecin, irinotecan, topotecan, etoposide, and mitoxantrone, did not inhibit the growth. Nevertheless, the first four of these compounds affected the morphology of C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…Topoisomerase is an enzyme that plays roles in the processes of DNA cleavage and recombination and is divided into two classes, I and II, based on the mode of DNA cleavage. Topoisomerase I cleaves one strand of a duplex DNA molecule, whereas topoisomerase II cleaves both strands of the DNA molecule [12]. Topoisomerase inhibitors are further classified into four classes chemically: camptothecins, anthracyclines, epipodophyllotoxins, and quinolones.…”
Section: Introductionmentioning
confidence: 99%